Loop ileostomy reversal after laparoscopic versus open rectal resection. Issue 3 (8th October 2018) - Sebastian, Arie; Stupart, Douglas; Watters, David A.
Abstract : Background: One of the potential advantages of laparoscopic abdominal surgery is in reducing the development of adhesions, making later surgery easier. The purpose of this study is to determine whether using the laparoscopic versus open approach for a rectal resection with a diverting ileostomy affects the speed and safety of subsequent ileostomy reversal. Methods: This is a retrospective study using patients who underwent ileostomy reversal following a rectal cancer resection with curative intent with a diverting ileostomy at the University Hospital Geelong between January 2006 and June 2017. Demographic information, operative technique and histological staging for the initial resection were recorded. Theatre time and complication rates for the ileostomy reversal were also recorded. Results: A total of 82 patients were included in this study (22 had laparoscopic resections as the primary operation, 50 had open resections and 10 had laparoscopic converted to open resections). The three groups were similar in age, body mass index, American Society of Anesthesiologists score and proportion undergoing chemoradiotherapy. Median (range) theatre time for ileostomy reversal was 118 (50–200) min after a laparoscopic resection, 80 (30–360) min after a laparoscopic converted to open resection and 65 (50–160) min after an open resection ( P = 0.009). Complication rates after ileostomy reversal were similar between the three groups ( P = 0.97). Conclusion: Ileostomy reversal took longer to perform if the primary rectal resection was performed laparoscopically.